1991
DOI: 10.1056/nejm199107043250103
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Sickle Cell Disease

Abstract: The "pain rate" (episodes per year) is a measure of clinical severity and correlates with early death in patients with sickle cell anemia over the age of 20. Even when the fetal hemoglobin level is low, one can predict that small increments in the level may have an ameliorating effect on the pain rate and may ultimately improve survival. This outcome is particularly encouraging to investigators studying hydroxyurea and other treatments designed to increase the fetal hemoglobin level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
491
3
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,391 publications
(515 citation statements)
references
References 18 publications
18
491
3
3
Order By: Relevance
“…Second, with modern medical care, individuals with SS can live up to adulthood and reproduce with a much less reduction in fitness than without modern medical care. For example, Platt et al (1994) found that the median age at death for individuals with sickle-cell anemia in the United States was 42 and 48 years for males and females, respectively (see similar results in Jamaica in Wierenga et al, 2001). As a result, in the absence of malaria and with modern medical care, the relative fitness levels of genotypes AA, AS and SS can generally be indicated by 1, 1 and 1-s. With these fitness levels, we can calculate how long it would take for selection (against SS homozygotes) to reduce frequency of the S allele from q 0 in generation 0 to q t in generation t using the following equation Hedrick, 2011a, p. 126).…”
Section: Sickle Cell S or B S Or Hbsmentioning
confidence: 78%
“…Second, with modern medical care, individuals with SS can live up to adulthood and reproduce with a much less reduction in fitness than without modern medical care. For example, Platt et al (1994) found that the median age at death for individuals with sickle-cell anemia in the United States was 42 and 48 years for males and females, respectively (see similar results in Jamaica in Wierenga et al, 2001). As a result, in the absence of malaria and with modern medical care, the relative fitness levels of genotypes AA, AS and SS can generally be indicated by 1, 1 and 1-s. With these fitness levels, we can calculate how long it would take for selection (against SS homozygotes) to reduce frequency of the S allele from q 0 in generation 0 to q t in generation t using the following equation Hedrick, 2011a, p. 126).…”
Section: Sickle Cell S or B S Or Hbsmentioning
confidence: 78%
“…1 As many of the complications of sickle cell anemia (homozygosity for HBB, glu6val), like osteonecrosis, acute chest syndrome and painful episode, are associated with the level of HbF, and, HbF is inversely associated with mortality, investigators have assiduously sought pharmacological means of increasing HbF production. [2][3][4][5][6] Hydroxyurea (HU), a ribonucleotide reductase inhibitor, is one drug that increases HbF concentration in patients with sickle cell anemia [7][8][9][10] and it is the sole FDA-approved agent for treating sickle cell anemia. Most, but not all patients respond to HU treatment with an increase in HbF, but as with the baseline HbF concentration, which varies widely among patients, the magnitude of the HbF response to HU is also variable.…”
Section: Introductionmentioning
confidence: 99%
“…2 The association of unusual or latent forms of CMD diagnosed by means of the EECs assay has been reported in a large number of patients with BCS or PVT. [3][4][5][6] Review of 51 published cases with BCS and 69 cases with portal and/or mesenteric vein thrombosis showed the presence of an overt CMD in 49% of the patients with BCS and 23% of the patients with portal/mesenteric vein thrombosis; the inclusion of patients with latent CMD as defined by the presence of EECs increased the diagnostic yield to 78% among patients with BCS and 48% among patients with portal/mesenteric vein thrombosis. 7 Therefore, we suggest that the exclusion of latent CMD as possible underlying cause of splanchnic vein thrombosis could have overestimated the role of inherited thrombophilia as a single risk factor for BCS or PVT.…”
Section: Acquired and Inherited Risk Factors For Splanchnic Venous Thmentioning
confidence: 99%
“…3 But few data exist regarding the relationship between acute leukocytosis and a sickle cell crisis, even though granulocytes may play an active role in vaso-occlusion. 4 In part, the difficulty in determining the significance reflects the complexity of a sickle cell crisis that may include a concurrent infection and frequent increases in multiple cytokines that can affect inflammation.…”
mentioning
confidence: 99%